Overexpression of MAC30 is Resistant to Platinum-Based Chemotherapy in Patients With Non-Small Cell Lung Cancer. (December 2016) - Chen, Ruhua; Fen, Yan; Lin, Xubo; Ma, Tieliang; Cai, Hourong; Ding, Hui
Adjuvant platinum-based chemotherapy has developed its stability as the first-line treatment in advanced non-small cell lung cancer (NSCLC). The objective of this study was to investigate the prognostic value of meningioma-associated protein (MAC30) on adjuvant platinum-based chemotherapeutic response and survival in patients with NSCLC. A total of 174 retrospective stage III B to IV Chinese patients with NSCLC were enrolled in the study. Among all cases, 85 patients were given platinum-based chemotherapy and another 89 patients received molecularly targeted therapy. The expression of MAC30 in tumor samples was confirmed via immunohistochemical staining to correlate with the therapeutic response and survival of patients. Patients having NSCLC with MAC30 overexpression showed a poorer response to platinum-based chemotherapy, while there was no prognostic value of MAC30 expression on molecularly targeted therapy. Further, patients receiving platinum-based chemotherapy with enhanced MAC30 expression exhibited shorter survival. A multivariate analysis exhibited that increased MAC30 expression was an independent prognostic factor for overall survival in patients having NSCLC with platinum-based chemotherapy. In conclusion, patients having NSCLC with higher MAC30 expression resisted to platinum-based chemotherapy and exhibited worse survival.